KNOWLEDGE, ATTITUDE AND PRACTICE TOWARDS THE USE AND CARE OF LONG-LASTING INSECTICIDAL NETS (LLINs) IN SIDOMULYO REGION PURWOREJO DISTRICT 2023 (Proceedings of the International Conference on Public Health, 2023)
LLINs are one of the interventions in malaria vector control. Although LLINs are considered effective for three years, the way in which they are used and maintained by users affects their physical and chemical durability. The purpose of this study was to determine the relationship between the level of knowledge and attitude with the practice of using and maintaining LLINs in Sidomulyo Region. The population of this study was 153 households, and the research sample was 117 households with the criteria that respondents were ≥ 17 years old and received KBTL in August - September 2022. The results showed that knowledge with p value
Keywords: LLINs; malaria; knowledge; attitudes